Analysis of the lncRNA–miRNA–mRNA Network Reveals a Potential Regulatory Mechanism of EGFR-TKI Resistance in NSCLC - Ding, Dandan; Zhang, Jufeng; Luo, Zhiming; Wu, Huazhen; Lin, Zexiao; Liang, Weicheng; Xue, Xingyang (Frontiers in Genetics, 2022)
Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are the most widely used for patients with positive epidermal growth factor receptor mutational lung cancer. Despite its initial therapeutic efficacy, most patients eventually develop drug resistance, which leads to poor prognosis in lung cancer patients. Studies have proved that non-coding RNAs including long non-coding RNAs (lncRNAs), circlular RNAs (circRNAs) and microRNAs (miRNAs) contribute to lung cancer by various biological functions, whereas how they regulate EGFR-TKIs resistance still remain unclear. In this study, we measured gene expression using microarray technology on gefitinib-resistant NSCLC cells to obtain differentially expressed (DE) lncRNAs and mRNAs. The 45 DE-lncRNAs associated with overall survival and 1799 target DE-mRNAs were employed to construct a core lncRNA-miRNA-mRNA network to predict the function in EGFR-TKIs resistance of NSCLC. We found the target DE-mRNAs were mainly enriched in pathways involved in EGFR-TKIs resistance. Especially, the target DE-mRNAs regulated by LINC01128 were significantly enriched in PI3K/Akt signaling pathway, where that the synergy of these target DE-mRNAs may play a key role in EGFR-TKIs resistance. Specially, the downregulated LINC01128, acting as a specific miRNA sponge, downregulates PTEN via sponging miR-25-3p. Furthermore, the signal response caused by the downregulation of PTEN would block PI3K/Akt signaling pathway, which may result in the development of drug resistance to EGFR-TKIs. Moreover, survival analysis showed the low expression of LINC01128 and PTEN was associated with poor prognosis in lung adenocarcinoma (LUAD). Therefore, LINC01128/miR-25-3p/PTEN axis may promote EGFR-TKIs resistance via PI3K/Akt signaling pathway, which provides new sights for the underlying molecular mechanisms of drug resistance to EGFR‐TKIs in NSCLC. Besides, our studies will help find some novel targets to overcome drug resistance of EGFR-TKIs in NSCLC.